ATP binding cassette G transporters and plant male reproduction. (3rd March 2016) - Zhao, Guochao; Shi, Jianxin; Liang, Wanqi; Zhang, Dabing
ABSTRACT: The function of ATP Binding Cassette G (ABCG) transporters in the regulation of plant vegetative organs development has been well characterized in various plant species. In contrast, their function in reproductive development particularly male reproductive development received considerably less attention till some ABCG transporters was reported to be associated with anther and pollen wall development in Arabidopsis thaliana and rice ( Oryza sativa ) during the past decade. This mini-review summarizes current knowledge of ABCG transporters regarding to their roles in male reproduction and underlying genetic and biochemical mechanisms, which makes it evident that ABCG transporters represent one of those conserved and divergent components closely related to male reproduction in plants. This mini-review also discusses the current challenges and future perspectives in this particular field.